Pacemakers and implantable cardioverter defibrillators - general and anesthetic considerations - Rapsang,Amy G. (2014)
A pacemaking system consists of an impulse generator and lead or leads to carry the electrical impulse to the patient's heart. Pacemaker and implantable cardioverter defibrillator codes were made to describe the type of pacemaker or implantable cardioverter defibrillator implanted. Indications for pacing and implantable cardioverter defibrillator implantation were given by the American College of Cardiologists. Certain pacemakers have magnet-operated reed switches incorporated; however, magnet application can have serious adverse effects; hence, devices should be considered programmable unless known otherwise. When a device patient undergoes any procedure (with or without anesthesia), special precautions have to be observed including a focused history/physical examination, interrogation of pacemaker before and after the procedure, emergency drugs/temporary pacing and defibrillation, reprogramming of pacemaker and disabling certain pacemaker functions if required, monitoring of electrolyte and metabolic disturbance and avoiding certain drugs and equipments that can interfere with pacemaker function. If unanticipated device interactions are found, consider discontinuation of the procedure until the source of interference can be eliminated or managed and all corrective measures should be taken to ensure proper pacemaker function should be done. Post procedure, the cardiac rate and rhythm should be monitored continuously and emergency drugs and equipments should be kept ready and consultation with a cardiologist or a pacemaker-implantable cardioverter defibrillator service may be necessary.